2006
DOI: 10.4315/0362-028x-69.12.2947
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Inactivation of Listeria monocytogenes and Escherichia coli O157:H7 Colony Biofilms by Micellar-Encapsulated Eugenol and Carvacrol

Abstract: The antimicrobial efficacy of carvacrol and eugenol, two essential oil compounds, encapsulated in a micellar nonionic surfactant solution on four strains of Listeria monocytogenes (Scott A, 101, 108, and 310) and four strains of Escherichia coli O157:H7 (H1730, E0019, F4546, and 932) growing as colony biofilms was investigated. Carvacrol and eugenol were encapsulated in Surfynol 485W at concentrations ranging from 0.3 to 0.9% (wt/wt) at a surfactant concentration of 5% (wt/wt). Colony biofilms were grown on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 50 publications
3
40
0
1
Order By: Relevance
“…However rifaximin promoted development (at all subletal concentrations) in EHEC O157:H7 and (at 75% MBC) in EAEC O104:H4. Application of micellar-encapsulated carvacrol at various concentrations has been inhibitory against surface growth of E. coli O157:H7 (P erez-Conesa et al, 2006). In our study, carvacrol at 75% MBC also reduced biofilm formation.…”
Section: Discussionsupporting
confidence: 49%
“…However rifaximin promoted development (at all subletal concentrations) in EHEC O157:H7 and (at 75% MBC) in EAEC O104:H4. Application of micellar-encapsulated carvacrol at various concentrations has been inhibitory against surface growth of E. coli O157:H7 (P erez-Conesa et al, 2006). In our study, carvacrol at 75% MBC also reduced biofilm formation.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, many lines of evidence have revealed that biofilm cells often exhibit unique physiological characteristics distinct from those of planktonic cells in liquid culture (Davey and O'Toole 2000;Romeo 2008;Annous et al 2009). Consistent with these expectations, we recently found that spontaneous lateral transfer of non-conjugative plasmids occurs in a colony biofilm [a type of biofilm that is formed on the air-solid surface (Mah et al 2003;Carmen et al 2004;Branda et al 2005;Perez-Conesa et al 2006)] of E. coli grown on common laboratory media, such as LB agar (Maeda et al 2006).…”
Section: Introductionmentioning
confidence: 57%
“…However, in the Wrst stage of this study and in a part of the second stage (single-species bioWlm), sessile cells of L. monocytogenes were more resistant to C. cassia EO and cinnamaldehyde than the cells of the gram-negative species used (EPEC). Similarly, Perez-Conesa et al [37] evaluated the antimicrobial eYcacy of encapsulated carvacrol and eugenol on strains of L. monocytogenes and E. coli O157: H7 in bioWlms and found that the gram-negative bacteria were more sensitive to the antimicrobial agents compared to the gram-positive bacteria. According to the studies of Rieu et al [38], van der Veen and Abee [39] and van der Veen and Abee [40], bioWlms formed by L. monocytogenes under conditions of constant Xow may have diVerent architecture and greater expression of genes related to the cellular stress response, which can cause an increase in resistance to antibacterial agents.…”
Section: Bacteriamentioning
confidence: 96%